Left Behind? The Impact of Leaves of Absence on Managers' Career Success - Judiesch, Michael K.; Lyness, Karen S. (Academy of Management Journal, 1999)
We examined the relationship between taking a leave of absence and rewards among 11,815 managers in a financial services organization. Results indicated that leaves of absence, regardless of the reason for them (family responsibilities or illness) or the gender of the manager, were associated with significantly fewer subsequent promotions and smaller salary increases. Leaves of absence had a significant, negative relationship to performance ratings only if the leaves had been taken during the year of the performance evaluation.